Association of genetic variants with primary angle closure glaucoma in two different populations. - Mona S Awadalla (Public Library of Science (PLoS), 2013)
Purpose A recent large genome-wide association study (GWAS) identified multiple variants associated with primary angle-closure glaucoma (PACG). The present study investigated the role of these variants in two cohorts with PACG recruited from Australia and Nepal. Method Patients with PACG and appropriate controls were recruited from eye clinics in Australia (n = 232 cases and n = 288 controls) and Nepal (n = 106 cases and 204 controls). Single nucleotide polymorphisms (SNPs) rs3753841 (COL11A1), rs1015213 (located between PCMTD1 and ST18), rs11024102 (PLEKHA7), and rs3788317 (TXNRD2) were selected and genotyped on the Sequenom. Analyses were conducted using PLINK and METAL. Results After adjustment for age and sex, SNP rs3753841 was found to be significantly associated with PACG in the Australian cohort (p = 0.017; OR = 1.34). SNPs rs1015213 (p = 0.014; OR 2.35) and rs11024102 (p = 0.039; OR 1.43) were significantly associated with the disease development in the Nepalese cohort. None of these SNPs survived Bonferroni correction (p = 0.05/4 = 0.013). However, in the combined analysis, of both cohorts, rs3753841 and rs1015213 showed significant association with p-values of 0.009 and 0.004, respectively both surviving Bonferroni correction. SNP rs11024102 showed suggestive association with PACG (p-value 0.035) and no association was found with rs3788317. Conclusion The present results support the initial GWAS findings, and confirm the SNP's contribution to PACG. This is the first study to investigate these loci in both Australian Caucasian and Nepalese populations.